Effects of day time sampling on the activities of termites in oil palm plantation at Malaysia-Indonesia - Andi Saputra; Madihah Halim; Nur-Atiqah Jalaludin; Izfa Riza Hazmi; Faszly Rahim (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
The activities and abundance of termites are highly affected by the environment. The objective of this study is to determine the activity of termites according to the different time of sampling event namely morning and evening session. The belt transects (100 metre length x 4 metre width) was set up in a line across the oil palm plantation. The sampling time was divided to the morning session (8:00 am to12:00 pm) and the evening session (2.00 pm to 6.00 pm). The presence of termites at each sampling time was recorded. A total of 12 belt transects with six replications for each sampling time at four different localities (MyFKT, MyLSK, IdFRGB, and IdCPSK) were placed. The results showed that the morning session recorded more species (31 species) in comparison to the evening session (15 species), and there are significant differences between the two sessions (χ2=45,119, df=30, p<0.05). Based on the autocorrelation, there are also significant differences on the termite’s activities between the two session. Overall, the termite activity is more active in the morning. The effect on the environment such as temperature and humidity in the morning and midday affect the abundance, diversity, and the presence of termites.